ZIF-8/graphene composite for photocatalytic degradation under low intensity UV irradiation and antibacterial applications - Manivel, Calvin Manasseh; Zheng, Alvin Lim Teik; Kannan, Renuga; Seenivasagam, Sivasangar; Yun Hin, Taufiq Yap; Boonyuen, Supakorn; Lease, Jacqueline; Andou, Yoshito; Tan, Kar Ban (Nature Research, 2025)
In this study, we synthesized a ZIF-8/graphene (Gr) composite and evaluated its photocatalytic degradation performance toward levofloxacin (LVX) under low-intensity UV light. The composite exhibited improved charge separation and enhanced reactive oxygen species (·OH, ·O2−, h+) generation compared to its individual components. Under optimal conditions (20 mg catalyst, 5 mg/L LVX, neutral pH), a 25.70% degradation was achieved after 120 min of irradiation, following pseudo-first-order (PFO) kinetics. While the degradation efficiency was modest, the catalyst operated effectively under low-energy conditions and demonstrated selective antibacterial activity against E. coli in dark conditions. These findings suggest that ZIF-8/Gr composites hold promise as dual-functional materials for pollutant mitigation and microbial control in niche wastewater applications, particularly where energy availability is limited. Further work is needed to enhance degradation efficiency and assess long-term operational stability.